PENGARUH LATIHAN PASSING VARIASI TERHADAP KEMAMPUAN PASSING ATLET FUTSAL DI EKTRAKURIKULER SEKOLAH DASAR KOTA BENGKULU - Ilahi, Bogy Restu; Nuryogatama, Muhammad; Wanda, Wahyu Trio (Dharmas Journal of Sport, 2024)
Bengkulu City's futsal growth demonstrates a high level of enthusiasm, both among children and adults. Futsal emphasizes basic skills, one of which is passing, which is very vital because almost 90% of futsal games involve passes between players. However, many athletes have difficulty in making accurate passes, which hinders the smoothness of the game. Monotonous training without variation can cause boredom and reduce motivation. Therefore, it is important to develop variation training to improve passing ability. The study looks into how various training techniques affect futsal players' passing skills in extracurricular activities at Elementary Schools in Bengkulu City. The study used an experimental method with a One Group Pre-test Post-test design and a sample of 37 athletes. The instruments used were passing and stopping tests. The results showed a significant increase in passing ability, with an increase of 54.66% and a training contribution of 92.16%. The results of the t-test showed a calculated t of -6.735 smaller than the t table of 1.688 at α = 0.05, which indicated that the alternative hypothesis was accepted. This study concludes that variation passing training is effective in improving the passing ability of futsal athletes in extracurricular activities at Elementary Schools in Bengkulu City.